TLR-4 ligation of dendritic cells is sufficient to drive pathogenic T cell function in experimental autoimmune encephalomyelitis - Mellanby Richard J (Journal of Neuroinflammation, 2012)
Abstract Background Experimental autoimmune encephalomyelitis (EAE) depends on the initial activation of CD4+ T cells responsive to myelin autoantigens. The key antigen presenting cell (APC) population that drives the activation of naïve T cells most efficiently is the dendritic cell (DC). As such, we should be able to trigger EAE by transfer of DC that can present the relevant autoantigen(s). Despite some sporadic reports, however, models of DC-driven EAE have not been widely adopted. We sought to test the feasibility of this approach and whether activation of the DC by toll-like receptor (TLR)-4 ligation was a sufficient stimulus to drive EAE. Findings Host mice were seeded with myelin basic protein (MBP)-reactive CD4+ T cells and then were injected with DC that could present the relevant MBP peptide which had been exposed to lipopolysaccharide as a TLR-4 agonist. We found that this approach induced robust clinical signs of EAE. Conclusions DC are sufficient as APC to effectively drive the differentiation of naïve myelin-responsive T cells into autoaggressive effector T cells. TLR-4-stimulation can activate the DC sufficiently to deliver the signals required to drive the pathogenic function of the T cell. These models will allow the dissection of the molecular requirements of the initial DC-T cell interaction in the lymphoid organs that ultimately leads to autoimmune pathology in the central nervous system.